A Hybrid Map with Permanent 3D Wireframes and Temporal Line Segments toward Long-Term Visual Localization. Issue 4 (1st July 2019) - Kaneko, Tomoya; Takahashi, Junji; Ito, Seiya; Tobe, Yoshito
Abstract : This paper deals with map-construction problems for visual localization. Basically, the map is an aggregation of visual landmarks, and it is desirable that such landmarks exist densely and permanently for long-term localization. However, there are no landmarks with these attributes at the same time. In order to solve this problem, we propose a hybrid map with permanent landmarks and temporal landmarks. As a permanent landmark, we employ 3D wireframe which can be easily obtained from architectural CAD. For a temporal landmark, we use line segments which are visually detected in images captured by a camera. To handle these two types of landmarks on the same map, we develop two algorithms. One is to extract temporal line segments from images containing two mixed landmarks, and the other is to reconstruct them into the 3D wireframe map. We experimentally demonstrated that the proposed hybrid map outperformed the 3D wireframe map in terms of localization accuracy.